Low-thermochemical-activity ceramic core for investment casting and preparation method of low-thermochemical-activity ceramic core
By using a combination of fused silica glass powder, thermochemical reaction inhibitors and combined mineralizers in the ceramic core, the problems of high-temperature decomposition of mineralizers and ceramic core reactions are solved, and the high-temperature performance of ceramic cores is significantly improved. The passing rate of castings.
Patent Information
- Application Number
- CN202411648929.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the high-temperature decomposition of mineralizers and the reaction of ceramic cores with high-temperature alloy melts leads to corrosion holes and pits in the inner cavity of the castings, reducing the product pass rate.
Using fused quartz glass powder as the matrix material, combined with thermochemical reaction inhibitor YZ-8 powder and yttrium zirconate powder, as well as a combination of mineralizer alumina powder and EC95 powder, low-thermal chemical activity is prepared by hot pressing and low-temperature strengthening process. Ceramic core.
It significantly improves the high-temperature thermochemical stability and mechanical properties of the ceramic core, effectively solves the shell liquid reaction problem of high-temperature alloy castings, and improves the quality and pass rate of the castings.
Smart Images

Figure BDA0005140451750000081 
Figure BDA0005140451750000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of investment casting, in particular to a low-thermochemically active ceramic core for investment casting and a preparation method thereof. Background Art
[0002] During the pouring process of directional / single crystal casting investment casting, the ceramic core must stay in the high-temperature alloy liquid at about 1500℃ for at least 1 hour. The active elements in the alloy melt are prone to complex physical and chemical interactions with the ceramic core. When the physical and chemical reaction process is serious, corrosion holes and pits will appear in the inner cavity of the casting, causing the casting to be scrapped. Silicon-based ceramic cores are widely used in the production of directional / single crystal blades because they are easy to remove and have moderate high-temperature mechanical properties. However, amorphous silicon dioxide or small, irregularly shaped quartz glass particles with sharp edges in silicon-based cores are prone to react with active metal elements at high temperatures, reducing the product qualification rate; while aluminum-based ceramic cores have more stable chemical properties and excellent high-temperature mechanical properties than silicon-based ceramic cores, but they are difficult to remove, and the waste liquid after removal is not easy to handle. Domestic precision casting companies rarely use them.
[0003] Patent CN202111628366.X discloses a silicon oxide-based ceramic core, the base material of which is quartz glass powder, and the mineralizers are zircon powder, alumina powder and calcium oxide powder. The powder contains 60% to 95% quartz glass powder, 1% to 30% zircon powder, 0.5% to 5% alumina powder, and 0.1% to 5% calcium carbonate powder by weight. Paraffin, beeswax, polyethylene and polyethylene glycol are used as hot injection molding plasticizers. The preparation method is to ball-mill the above powders to mix them evenly, put them into the molten plasticizer for mixing, and hot-press mold them on a ceramic core molding machine. Before injection molding, a quartz glass rod / tube is pre-placed in the core mold at the position corresponding to the thick core section. The ceramic core formed by hot injection molding is trimmed and calibrated and then placed in a box-type resistance furnace for baking. The prepared silicon oxide-based ceramic core has the characteristics of high high-temperature strength, good creep resistance, small sintering shrinkage, stable size and high core removal efficiency.
[0004] However, the above technical solution still has the following deficiencies: (1) zircon powder, which is a more common mineralizer, is used as a mineralizer. The impurity elements contained in zircon powder are as many as more than 10 kinds of impurity elements, which are impurities of the mineral itself and are difficult to extract. The impurity elements will reduce the high temperature performance of the core during the high temperature casting process. The main component of zircon powder, zirconium silicate, will theoretically decompose into zirconium oxide and silicon oxide at around 1540°C. Due to the presence of impurity elements, the actual decomposition temperature is lower. During the single crystal directional casting process, the core is immersed in high temperature molten steel for a long time, and the zircon powder tends to decompose. (2) The above technical solution uses analytical pure alumina, whose main crystal phase is α-alumina. Although it can achieve the purpose of high temperature resistance, in its crystal structure, oxygen ions are arranged in a hexagonal close stacking, and aluminum ions are symmetrically distributed in the octahedral coordination center surrounded by oxygen ions. This structure makes α-alumina have an extremely high melting point and low chemical activity. When added to quartz glass powder, the mineralization sintering and mullite conversion rate are low. Summary of the invention
[0005] In view of this, the present invention proposes a low thermochemically active ceramic core for investment casting and a preparation method thereof to solve the problem in the prior art that the mineralizer decomposes at high temperature and easily causes core-liquid reaction in the casting, thereby affecting the qualified rate of the ceramic core.
[0006] The technical solution of the present invention is achieved in this way:
[0007] The invention provides a low thermochemical activity ceramic core for investment casting. The ceramic core comprises the following chemical components by weight percentage: 70-90wt% of fused quartz glass powder, 3-15wt% of thermochemical reaction inhibitor and 7-15wt% of combined mineralizer.
[0008] In the present invention, fused quartz glass powder is used as the matrix material of the ceramic core to provide the main structure and strength of the core, and has good high-temperature stability and heat resistance; the combined mineralizer improves the solid-phase and liquid-phase sintering performance of the core, promotes the uniform distribution of the solid-liquid phase sintering of the ceramic core, and stabilizes the high-temperature performance of the core; the addition of the thermochemical inhibitor helps to improve the thermochemical stability of the core and reduce the reaction with the high-temperature alloy melt.
[0009] On the basis of the above technical solution, preferably, the thermochemical reaction inhibitor includes YZ-8 powder and yttrium zirconate powder, and the combined mineralizer includes alumina powder and EC95 powder.
[0010] In the present invention, an alumina-based mineralizer is used, wherein EC95 powder, i.e., fused mullite powder, is an fused material with a stable mullite crystal phase. On the basis of promoting the sintering of quartz glass and improving the high-temperature performance of the core, the initial mullite crystal can separate the quartz phase transformed by the quartz glass, inhibit the flow of the glass phase at high temperature, so that the stress generated by the volume change of quartz during heating and cooling is released and the high-temperature performance of the core is improved. YZ-8 powder and yttrium zirconate powder are used as thermochemical reaction inhibitors, wherein YZ-8 is 8% yttria-stabilized zirconium oxide, and its high-temperature performance is relatively stable. It can maintain a stable crystal structure during the core sintering process, participate in the solid-phase sintering of the core, and can retain the stability of its high-temperature performance, thereby improving the stability of the core; yttrium zirconate also has a high high-temperature stability, and does not chemically react with the melt during the high-temperature casting process, which can improve the high-temperature thermochemical stability of the core. Yttrium zirconate and YZ-8 work together to improve the solid-phase sintering performance of the core, making the solid-liquid phase sintering of the ceramic core more evenly distributed, while stabilizing the high-temperature performance of the core.
[0011] On the basis of the above technical solution, preferably, the mass ratio of YZ-8 powder and yttrium zirconate powder in the thermochemical reaction inhibitor is (4-8):1.
[0012] On the basis of the above technical solution, preferably, the mass ratio of alumina powder to EC95 powder in the combined mineralizer is 1:(3-6).
[0013] On the basis of the above technical solution, preferably, the Al2O3 content of the electromelting material in the EC95 powder is 94-97wt%, and the SiO2 content is 3-6wt%.
[0014] On the basis of the above technical solution, preferably, the particle size of the alumina powder is 5-7 μm.
[0015] Specifically, the main crystal phase of activated alumina is γ-alumina, whose oxygen ions are densely packed with approximately cubic face centers, and aluminum ions are irregularly distributed in the octahedral and tetrahedral voids surrounded by oxygen ions. This structure makes the γ-alumina powder have a larger specific surface area and higher activity, which can promote the sintering of quartz glass and produce stable high-refractory mullite crystals at a lower sintering temperature. At the same time, the fine powder allows the produced mullite to be evenly dispersed inside the core, thereby improving the high-temperature performance of the core.
[0016] The present invention provides a method for preparing a low thermochemically active ceramic core for investment casting, comprising the following steps:
[0017] Fused quartz glass powder, thermochemical reaction inhibitor and combined mineralizer are weighed in proportion and mixed evenly to form a thermoplastic slurry, which is formed by hot pressing. The obtained core wet blank is calcined, immersed in an inert solvent, dried and then strengthened at low temperature to obtain a low thermochemical activity ceramic core.
[0018] On the basis of the above technical scheme, preferably, the inert solvent is an acidic aluminum sol, the aluminum oxide content in the acidic aluminum sol is 15-20wt%, the inert solvent is placed in a strengthening device with a vacuum function, the core is placed in the inert solvent, the strengthening cabin is closed and vacuumed, the pressure in the cabin is controlled at 0.85-0.95bar, and the immersion time is ≥1h.
[0019] On the basis of the above technical solution, preferably, the process parameters of the hot pressing method include: injection pressure of 20-50 bar, temperature of 60-80° C.; roasting temperature of the core wet blank of 1180-1220° C., roasting time of 3-6 h.
[0020] The invention provides an application of a low-thermochemically active ceramic core in preparing a directional / single crystal casting.
[0021] The low thermochemically active ceramic core for investment casting of the present invention has the following beneficial effects compared with the prior art:
[0022] (1) The low thermochemical activity ceramic core and the preparation method thereof provided by the present invention significantly improve the high temperature thermochemical stability and mechanical properties of the ceramic core by adding a thermochemical reaction inhibitor and a combined mineralizer, can effectively solve the shell-liquid reaction problem of high temperature alloy castings, meet the strict requirements of directional / single crystal high temperature alloy investment casting, improve the quality and qualified rate of castings, and provide reliable technical support for the production of directional / single crystal castings of high temperature alloys for aircraft engines;
[0023] (2) The combined mineralizer formed by activated alumina powder and EC95 powder can not only promote the sintering of quartz glass, but also generate stable mullite crystals with high refractoriness at a relatively low temperature. The mullite crystal phase in EC95 powder can separate the quartz phase transformed by quartz glass, inhibit the flow of the glass phase at high temperature, and release the stress generated by the volume change of quartz when heating and cooling; the activated alumina powder can be evenly distributed inside the core, further improving the high-temperature performance of the core. This combined effect significantly improves the microstructure, thermal stability and high-temperature mechanical properties of the ceramic core, and effectively solves the problem that traditional silicon-based ceramic cores are prone to react with active metal elements at high temperatures.
[0024] (3) The high-temperature thermochemical stability of the ceramic core is significantly improved by forming a thermochemical reaction inhibitor with YZ-8 powder and yttrium zirconate powder. YZ-8 has the characteristics of stable high-temperature performance. It can maintain a stable crystal structure during the core sintering process, participate in the solid-phase sintering of the core, and retain the stability of its high-temperature performance. Yttrium zirconate also has high high-temperature stability and does not chemically react with the melt during high-temperature casting. The combined effect of the two not only improves the solid-phase sintering performance of the core, making the solid-liquid phase sintering of the ceramic core more evenly distributed, but also significantly enhances the high-temperature thermochemical stability of the core, effectively solving the problem that traditional silicon-based ceramic cores are prone to react with active metal elements at high temperatures, and improving the quality and pass rate of high-temperature alloy castings. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available.
[0027] Among them: fused quartz glass powder was purchased from Jinzhou Xihui Quartz Technology Co., Ltd.; YZ-8 particle size D50 is 15μm; activated alumina powder particle size is 5-7μm; EC95 powder electromelted Al 2 O 3 The content is 94-97wt%, SiO 2 The content is 3-6wt%.
[0028] Example 1
[0029] This embodiment provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0030] 16 kg of fused quartz glass powder, 0.8 kg of YZ-8 powder, 0.2 kg of yttrium zirconate powder, 0.6 kg of activated alumina powder, and 2.4 kg of EC95 powder were weighed, put into a V-type mixer and mixed evenly, and then added into a core slurry mixer to prepare a thermoplastic slurry.
[0031] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 35 bar and the slurry temperature is 75°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1200°C for 4.5 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening chamber is closed and vacuumed. The pressure in the chamber is controlled at 0.9 bar. The chamber is soaked for 1 hour, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0032] Example 2
[0033] This embodiment provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0034] 14 kg of fused quartz glass powder, 2.4 kg of YZ-8 powder, 0.6 kg of yttrium zirconate powder, 0.75 kg of activated alumina powder, and 2.25 kg of EC95 powder were weighed, put into a V-type mixer and mixed evenly, and then added into a core slurry mixer to prepare a thermoplastic slurry.
[0035] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 40 bar and the slurry temperature is 60°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1180°C for 6 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening chamber is closed and vacuumed. The pressure in the chamber is controlled at 0.85 bar. The ceramic core product is soaked for 3 hours, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0036] Example 3
[0037] This embodiment provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0038] Weigh 18 kg of fused quartz glass powder, 0.53 kg of YZ-8 powder, 0.07 kg of yttrium zirconate powder, 0.2 kg of activated alumina powder, and 1.2 kg of EC95 powder, put the above materials into a V-type mixer and mix them evenly, and then add them into a core slurry mixer to prepare a thermoplastic slurry.
[0039] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 50 bar and the slurry temperature is 80°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1220°C for 3 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening cabin is closed and vacuumed. The pressure in the cabin is controlled at 0.95 bar. The core is soaked for 3 hours, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0040] Example 4
[0041] This embodiment provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0042] 16.4 kg of fused quartz glass powder, 1.67 kg of YZ-8 powder, 0.33 kg of yttrium zirconate powder, 0.32 kg of activated alumina powder, and 1.28 kg of EC95 powder were weighed, put into a V-type mixer and mixed evenly, and then added into a core slurry mixer to prepare a thermoplastic slurry.
[0043] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 40 bar and the slurry temperature is 74°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1190°C for 5 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening cabin is closed and vacuumed. The pressure in the cabin is controlled at 0.9 bar. The core is soaked for 2 hours, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0044] Comparative Example 1
[0045] This comparative example provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0046] 16 kg of fused quartz glass powder, 1.0 kg of YZ-8 powder, 0.6 kg of activated alumina powder, and 2.4 kg of EC95 powder were weighed, put into a V-type mixer and mixed evenly, and then added into a core slurry mixer to prepare a thermoplastic slurry.
[0047] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 35 bar and the slurry temperature is 75°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1200°C for 4.5 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening chamber is closed and vacuumed. The pressure in the chamber is controlled at 0.9 bar. The chamber is soaked for 1 hour, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0048] Comparative Example 2
[0049] This comparative example provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0050] 16 kg of fused quartz glass powder, 0.8 kg of YZ-8 powder, 0.2 kg of yttrium zirconate powder, and 3.0 kg of EC95 powder were weighed, put into a V-type mixer and mixed evenly, and then added into a core slurry mixer to prepare a thermoplastic slurry.
[0051] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 35 bar and the slurry temperature is 75°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1200°C for 4.5 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening chamber is closed and vacuumed. The pressure in the chamber is controlled at 0.9 bar. The chamber is soaked for 1 hour, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0052] Comparative Example 3
[0053] This comparative example provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0054] Weigh 12 kg of fused quartz glass powder, 3.2 kg of YZ-8 powder, 0.8 kg of yttrium zirconate powder, 0.8 kg of activated alumina powder, and 3.2 kg of EC95 powder, put the above materials into a V-type mixer and mix them evenly, then add them into a core slurry mixer to prepare a thermoplastic slurry.
[0055] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 35 bar and the slurry temperature is 75°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1200°C for 4.5 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening chamber is closed and vacuumed. The pressure in the chamber is controlled at 0.9 bar. The chamber is soaked for 1 hour, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0056] Comparative Example 4
[0057] This comparative example provides a low thermochemically active ceramic core for investment casting and a preparation method thereof, comprising the following steps:
[0058] Weigh 14 kg of fused quartz glass powder, 1.75 kg of YZ-8 powder, 0.25 kg of yttrium oxide powder, 0.6 kg of activated alumina powder, and 3.4 kg of EC95 powder, put the above materials into a V-type mixer and mix them evenly, then add them into a core slurry mixer to prepare a thermoplastic slurry.
[0059] The thermoplastic slurry is hot-pressed by a high-pressure core press machine using a hot-pressing method. The injection pressure of the hot-pressing method is 35 bar and the slurry temperature is 75°C. The wet core blank formed by the hot-pressing method is calcined at a temperature of 1200°C for 4.5 hours. The acid aluminum sol is placed in a strengthening device with a vacuum function, and the calcined wet core blank is immersed in the acid aluminum sol. The strengthening chamber is closed and vacuumed. The pressure in the chamber is controlled at 0.9 bar. The chamber is soaked for 1 hour, and then taken out and dried for low-temperature strengthening to obtain a ceramic core product.
[0060] Performance Testing
[0061] The performance of the ceramic core products prepared in the embodiments and comparative examples was tested. The room temperature flexural strength and high temperature flexural strength (1550°C) were tested according to the aviation industry standard HB5353.3-2004; the high temperature deflection (1550°C) was measured according to the aviation industry standard HB5353.4-2004; the firing shrinkage was measured according to the aviation industry standard HB5353.2-2004. The test results are shown in Table 1.
[0062] Table 1 Core performance
[0063]
[0064]
[0065] It can be seen from Table 1 that the low thermochemically active ceramic core prepared by the technical solution of the embodiment of the present invention has strong room temperature flexural strength, especially better flexural strength and deflection at high temperature, and smaller sintering shrinkage; the technical solution of the embodiment of the present invention reduces the sintering cracking tendency of the low thermochemically active ceramic core and ensures the quality of the ceramic core products.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low thermochemically active ceramic core for investment casting, characterized in that: The ceramic core comprises the following chemical components by weight percentage: 70-90 wt % of fused silica glass powder, 3-15 wt % of thermochemical reaction inhibitor and 7-15 wt % of combined mineralizer.
2. A low thermochemically active ceramic core for investment casting according to claim 1, characterized in that: The thermochemical reaction inhibitor comprises YZ-8 powder and yttrium zirconate powder, and the combined mineralizer comprises alumina powder and EC95 powder.
3. A low thermochemically active ceramic core for investment casting as claimed in claim 2, characterized in that: The mass ratio of YZ-8 powder to yttrium zirconate powder in the thermochemical reaction inhibitor is (4-8):
1.
4. A low thermochemically active ceramic core for investment casting as claimed in claim 2, characterized in that: The mass ratio of alumina powder to EC95 powder in the combined mineralizer is 1:(3-6).
5. A low thermochemically active ceramic core for investment casting as claimed in claim 2, characterized in that: The EC95 powder contains 94-97wt% Al2O3 and 3-6wt% SiO2 in the electromelting material.
6. A low thermochemically active ceramic core for investment casting as claimed in claim 2, characterized in that: The particle size of the alumina powder is 5-7 μm.
7. A method for preparing a low thermochemically active ceramic core for investment casting according to any one of claims 1 to 6, characterized in that: The steps include: Fused quartz glass powder, thermochemical reaction inhibitor and combined mineralizer are weighed in proportion and mixed evenly to form a thermoplastic slurry, which is formed by hot pressing. The obtained core wet blank is calcined, immersed in an inert solvent, dried and then strengthened at low temperature to obtain a low thermochemical activity ceramic core.
8. The method for preparing a low thermochemically active ceramic core for investment casting according to claim 7, characterized in that: The inert solvent is acidic aluminum sol, the aluminum oxide content in the acidic aluminum sol is 15-20wt%, the inert solvent is placed in a strengthening device with a vacuum function, the core is placed in the inert solvent, the strengthening chamber is closed and vacuumed, the pressure in the chamber is controlled at 0.85-0.95bar, and the immersion time is ≥1h.
9. The method for preparing a low thermochemically active ceramic core for investment casting according to claim 7, characterized in that: The process parameters of the hot pressing method include: injection pressure of 20-50 bar, temperature of 60-80° C.; roasting temperature of the core wet blank of 1180-1220° C., roasting time of 3-6 hours.
10. Use of a low thermochemically active ceramic core for investment casting as claimed in any one of claims 1 to 6 in the preparation of directional / single crystal castings.
Citation Information
Patent Citations
Porous silicon-based ceramic core suitable for double-wall blades and preparation method of core
CN109734430A
Preparation method of silicon-based ceramic core with high dimensional stability at high temperature
CN109928739A
Silicon oxide-based ceramic core for large-size directional hollow blade of heavy-duty gas turbine and preparation of silicon oxide-based ceramic core
CN114249588A
Anti-cracking inert ceramic core and preparation method thereof
CN116102364A
Casting cores and methods for making
US20160144423A1